The littlest light on the Christmas tree [videorecording (DVD)] - Seymour, Jane, 1951-; Naughton, James, 1945- (Abrams Gentile Entertainment, 2004)
This is a timeless, magical tale about two unforgettable friends, an abandoned discarded Christmas bulb, afraid and alone-and an eight-year-old boy who finds him and takes him home. When the town suffers a blackout from a fierce winter storm, Little Light triumphs over all odds. Includes six original songs with sing-a-long.